Effect of hyperbaric oxygen therapy in rats with subtotal splenectomy preserving the inferior pole - Paulo,Marcela Souza Lima (2011)
PURPOSE: To evaluate the effect of hyperbaric oxygen therapy on the survival and weight of rats submitted to subtotal splenectomy and on the viability and growth of the inferior pole. METHODS: Forty Wistar rats underwent subtotal splenectomy with preservation of the inferior pole and distributed into two groups: Group A (n=20) - not treated with hyperbaric oxygen, Group B (n=20) - treated with hyperbaric oxygen. These groups were divided into two subgroups of 10 animals each, according to the time of euthanasia, 15th and 45th days. The survival and weight of the animals were recorded. The inferior pole was measured, weighed and morphologically analyzed. RESULTS: All animals survived. The weight of the animals increased in all subgroups, but decreased on the 10th day in the subgroups treated with hyperbaric oxygen (p<0.001). The viability of the inferior pole was more evident in animals treated on the 15th day, but did not differ on the 45th day. The growth of the inferior pole has not occurred on the 15th day but on the 45th day after surgery in untreated animals (p<0.01) and treated animals (p<0.05). Vascular and cellular increase in treated animals was significantly higher than in untreated ones. CONCLUSION: Hyperbaric oxygen therapy did not affect the survival of animals but reduced their weight. It improved the viability of the inferior splenic pole, but did not interfere with their growth.